Evaluation and protection of multi-level location privacy based on an information theoretic approach - Wenjing ZHANG; Qiao LIU; Hui ZHU (Tongxin xuebao)
A privacy metric based on mutual information was proposed to measure the privacy leakage occurred when location data owner trust data users at different levels and need to publish the distorted location data to each user according to her trust level,based on which an location privacy protection mechanism (LPPM)was generated to protect user’s location privacy.In addition,based on mutual information,a metric was proposed to measure the privacy leakage caused by attackers obtaining different levels of distorted location data and then performing inference attack on the original location data more accurately.Another privacy metric was also proposed to quantify the information leakage occurred in the scenario based on mutual information.In particular,the proposed privacy mechanism was designed by modifying Blahut-Arimoto algorithm in rate-distortion theory.Experimental results show the superiority of the proposed LPPM over an existing LPPM in terms of location privacyutility tradeoff in both scenarios,which is more conspicuous when there are highly popular locations.